Membrane technology in microalgae harvesting for biofuel production - Nur Hidayah, Mat Yasin (2014)
Microalga has emerged as one of the most promising alternatives sources of lipid for use in biodiesel production because of their high growth rates and productivity to produce biomass compared to other generations of biodiesel feedstocks. In this study, Chiorella vulgaris was selected as the model microalga. The most important issue to be addressed is the recovery process of Chiorella vulgaris biomass that can be substantially more expensive than the culturing of the microalgae. Therefore, Chiorella vulgaris harvesting is an important research area in order to develop an appropriate and economical process for microalgae species so that the production of this biodiesel is competitive. Detailed studies on the effectiveness of membrane filtration for the separation of Chiorella vulgaris biomass from the culture medium had been carried out. The hydrophilic cellulose acetate membrane with pore diameter of 1.2 pm exhibited the best performances among four membranes tested (cellulose nitrate, polypropylene and polyvinylidenefluoride) in terms of permeation flux. The optimal conditions achieved were 1.5 bar of transmembrane pressure (TMP) and 0.4 ms -1 of crossflow velocity (CFV). In addition, 0.75% sodium hypochloride (NaOC1) at 60 °C was performed as the membrane cleaning process. The concentration polarization (CP) thickness was found to be strongly depended on the membrane surface charge and the number of membrane cleaning cycles. The microalgae-membrane interaction was successfully achieved by XDLVO approach. Finally, the microfiltration method was compared with c entrifugation and coagulation method to determine the most efficient method for separating Chiorella vulgaris biomass from the culture medium. Of the three harvesting methods described in this work, it was found that the membrane microfiltration was more effective in harvesting process because it allowed the handling of large volumes of culture at a low energy costs. Similar fatty acid (FAME) profiles were obtained for all of the harvesting methods, indicating that the main components were palmitic acid (C16:0), oleic acid (C18:1) and linoleic acid (C18:2). However, the amounts of the individual FAME were higher for microfiltration than for centrifugation and coagulation; coagulation performed the most poorly in this regard by producing the smallest amount of FAME (41.61 ± 6.49 mgfg dw). The unsaturated FAME (C 16:1, C 18:1, C 18:2, C 18:3) were predominant in the FAME profile (>70%) for all harvesting methods applied and thus making Chiorella vulgaris biomass a good species for biodiesel production.